The Semiotic Shield: A Multi-Generational Structural Equation Modeling Analysis of Linguistic Resistance and Digital Agency in Indonesia’s Post-Truth Era - Gayatri Putri; Aaliyah El-Husaini; Farah Faiza (HM Publisher, 2025)
In the Indonesian post-truth landscape, digital discourse is frequently saturated with misinformation and polarized rhetoric. This study investigates how Gen Alpha and Gen Z employ unique linguistic markers—commonly termed slang—not merely as casual communication but as a subversive tool to navigate and resist dominant socio-political narratives. Using a mixed-methods approach, we analyzed a corpus of 50,000 interactions across TikTok and X between January 2024 and June 2025. Natural Language Processing and Critical Discourse Analysis were integrated with Structural Equation Modeling to establish linguistic subversion indices across different age cohorts. Findings indicate that slang terms such as fufufafa and cek khodam serve as shibboleths that foster community in-grouping while delegitimizing institutional authority. Statistical modeling reveals a strong correlation (r = 0.74) between slang density and the deconstruction of hoax narratives. Specifically, a 1-unit increase in slang versatility predicts a 0.82 increase in a user’s ability to identify astroturfing. In conclusion, the study concludes that youth digital lects function as a form of semiotic guerrilla warfare, providing a mechanism for political agency in an era of truth decay. This linguistic resistance effectively renders misinformation powerless by labeling it as socially irrelevant or cringe.